\(C=\frac{3}{7}\times\frac{4}{13}+\frac{3}{7}\times\frac{9}{13}+5\frac{4}{7}\)
\(C=\frac{3}{7}\times\frac{4}{13}+\frac{3}{7}\times\frac{9}{13}+\frac{39}{7}\)
\(C=\frac{3}{7}\times\left(\frac{4}{13}+\frac{9}{13}\right)+\frac{39}{7}\)
\(C=\frac{3}{7}\times1+\frac{39}{7}\)
\(C=\frac{3}{7}+\frac{39}{7}\)
\(C=\frac{42}{7}\)
\(C=6\)
_Chúc bạn học tốt_
\(C=\frac{3}{7}\cdot\frac{4}{13}+\frac{3}{7}\cdot\frac{9}{13}+5\frac{4}{7}\)
\(C=\frac{3}{7}\cdot\frac{4}{13}+\frac{3}{7}\cdot\frac{9}{13}+\frac{39}{7}\)
\(C=\left(\frac{4}{13}+\frac{9}{13}\right)\cdot\frac{3}{7}+\frac{39}{7}\)
\(C=1\cdot\frac{3}{7}+\frac{39}{7}\)
\(C=\frac{3}{7}+\frac{39}{7}\)
\(C=\frac{46}{7}\)
Ta có :
\(C=\frac{3}{7}.\frac{4}{13}+\frac{3}{7}.\frac{9}{13}+5\frac{4}{7}\)
\(\Rightarrow C=\frac{3}{7}.\left(\frac{4}{13}+\frac{9}{13}\right)+\frac{39}{7}\)
\(\Rightarrow C=\frac{3}{7}.\frac{13}{13}+\frac{39}{7}\)
\(\Rightarrow C=\frac{3}{7}.1+\frac{39}{7}\)
\(\Rightarrow C=\frac{3}{7}+\frac{39}{7}\)
\(\Rightarrow C=\frac{42}{7}\)
\(\Rightarrow C=6\)
Vậy \(C=6\)
~ Ủng hộ nhé